The history of World War I in photographs - Hamilton, R. (Robert) (Parragon, 2014)
World War I wrought global devastation, destroying empires and the lives of tens of millions. The symbol of the madness that gripped the great powers between 1914 and 1918 was the trench system on the Western Front, where men died in tens of thousands over a few miles of butchered landscape, where the machine gun was king. The many sides of the conflict, both military and civilian, are captured in these pages: the crowded, shell-drenched beaches at Gallipoli in 1915: a British battleship blown apart at Jutland in 1916; the sea of mud that was Passchendaele in 1917; the lumbering tanks which helped break the spirit of the German Army in 1918. Superbly illustrated with photographs from the Daily Mail archives these pages capture a defining moment in world history."--Back cover